ANALYSIS OF THE APPLICATION OF FINANCIAL ACCOUNTING STANDARD STATEMENT NO 226 CONCERNING PENSION FUND ACCOUNTING IN UNISBA PENSION FUNDS - Diamonalisa Sofianty; Elly Halimatusadiah; Yuni Rosdiana; Mardini, Riyang (Kajian Akuntansi, 2024)
Pension Funds are benefits given to employees after their work period. Pension funds can be in the form of a Defined Benefit Pension Plan or a Defined Contribution Pension Plan. Management can be carried out by financial institutions and employers. The Unisba Pension Fund is managed using the Defined Benefit Pension Program method, with the preparation of Financial Reports in accordance with the format regulated in Financial Accounting Standards Statement PSAK 226  so that it is transparent and accountable. The aim of this research is to compare the financial statements of the Unisba Pension Fund with PSAK 226. The method used is qualitative descriptive research. The research results show that the accounting reporting implemented by the Unisba Pension Fund as a whole is in accordance with the applicable PSAK No. 226. Keywords    : PSAK No. 226, Pension Funds, Financial Report.